Validation of a new reference values’s database for semiquantification of 123I‐FP‐CIT SPECT scans in one nuclear medicine department - Elias, Madalena (2015)
The DatScanTM and its Semiquantification (SQ) can provide advantages in the diagnosis of Parkinsonian Syndromes (PS). To improve the SQ is recommended the creation of adapted database (DB) with reference values for the Nuclear Medicine Departments. Previously to this work was created a adapted database (DBRV) to Nuclear Medicine Department's protocol and population of Infanta Cristina's Hospital located in Badajoz, for patients between the ages of 60 and 75, and reference values of the SQ were calculated. Aim: To evaluate the discrimination capacity of a department's adapted DB reference's values of healthy controls for DatScanTM.